Secure Attachment Representation in Adolescence Buffers Heart-Rate Reactivity in Response to Attachment-Related Stressors - Gander, Manuela; Karabatsiakis, Alexander; Nuderscher, Katharina; Bernheim, Dorothee; Doyen-Waldecker, Cornelia; Buchheim, Anna (Frontiers in Human Neuroscience, 2022)
To date, we know very little about the effects of the differences in attachment classifications on the physiological correlates of stress regulation in adolescent age groups. The present study examined for the first time heart rate (HR) and heart rate variability (HRV) during an attachment interview in adolescents. HR and HRV data were collected during a baseline assessment as well as during the administration of the Adult Attachment Projective Picture System (AAP) in a community-based sample of 56 adolescents (26 females and 30 males, mean age = 16.05 years [SD =1.10]). We additionally used the Adult Attachment Interview (AAI) in 50% of our sample to test the convergent validity. Adolescents with a secure attachment representation showed a higher HRV from baseline to the AAP interview compared to those with an insecure-dismissing and the unresolved group. A comparison between the two insecure attachment groups showed no significant difference related to HR and HRV. Cohen’s Kappa (κ = .81) revealed an almost perfect agreement between the AAP and the AAI for the four-group classification. Our results indicate that adolescents with a secure attachment representation are more capable of dealing with attachment-related distress which is represented in higher HRV during an attachment interview.